2020
DOI: 10.3390/brainsci10120983
|View full text |Cite
|
Sign up to set email alerts
|

Factors Modifying the Amount of Neuroanatomical Overlap between Languages in Bilinguals—A Systematic Review of Neurosurgical Language Mapping Studies

Abstract: Neurosurgery on individuals with lesions around language areas becomes even more complicated when the patient is bilingual. It is thus important to understand the principles that predict the likelihood of convergent versus separate neuroanatomical organization of the first (L1) and the second language (L2) in these individuals. We reviewed all English-language publications on neurosurgical language mapping in bilinguals before January 2020 in three databases (e.g., PubMed). Our search yielded 28 studies with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 66 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…Moreover, a study [92] involving bilingual patients with brain tumors found that fMRI language mapping performed in both languages provided a superior appreciation of the language network than mapping in only one language (i.e., more language-related regions were identified). This finding has been confirmed by a recent systematic review of studies with patients (including individuals with brain tumors) who underwent neurosurgical language mapping (pre-operative fMRI, Wada, and/or electrical stimulation mapping) [93]. (b) Language characteristics-in comparison to most languages from the Indo-European family (e.g., English, French, Spanish), some non-Indo-European languages have been associated with weaker fMRI language dominance [94].…”
Section: Linguistic Factorsmentioning
confidence: 52%
“…Moreover, a study [92] involving bilingual patients with brain tumors found that fMRI language mapping performed in both languages provided a superior appreciation of the language network than mapping in only one language (i.e., more language-related regions were identified). This finding has been confirmed by a recent systematic review of studies with patients (including individuals with brain tumors) who underwent neurosurgical language mapping (pre-operative fMRI, Wada, and/or electrical stimulation mapping) [93]. (b) Language characteristics-in comparison to most languages from the Indo-European family (e.g., English, French, Spanish), some non-Indo-European languages have been associated with weaker fMRI language dominance [94].…”
Section: Linguistic Factorsmentioning
confidence: 52%
“…In general, clinical observations on multilingual aphasic individuals documented different patterns of impairment and of post-insult recovery in each of the languages spoken by the patients and described complex correlations between language and brain sites (Albert and Obler, 1978;Aglioti and Fabbro, 1993;Paradis, 2000;Giussani et al, 2007). Consistent findings were reported in neurosurgical settings where multilingual patients showed language-specific 2 responses to brain stimulation (see Połczyñska and Bookheimer, 2020 for a recent review). These data have often been used as evidence that different languages are represented in different brain regions.…”
Section: Introductionmentioning
confidence: 65%
“…The linguistic profiles of multilingual speakers are very heterogeneous, since a multitude of experience-related factors determines the multilingual competence: age (early vs. late) and type of acquisition (formal vs. informal education; simultaneous vs. sequential acquisition), amount of exposure to the different languages, modality (oral vs. written or both) and context (familiar vs. professional or both) of use, proficiency level, and degree of similarity/distance between languages. Recent reviews and meta-analyses (Cargnelutti et al, 2019;Połczyñska and Bookheimer, 2020) have shown that those factors affect the performance of multilinguals in linguistic tasks and have an impact on the neural organization of languages. In addition, the interaction among the spoken languages has been shown to modulate their neural underpinnings (De Bot, 2004;Kroll and Bialystok, 2013;Kroll and Ma, 2018;Del Maschio and Abutalebi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For bilingual and multilingual neurosurgical patients affected by lesion located in language-eloquent areas, the preoperative mapping and languages preservation represent an additional major goal. At present, bilingual (and multilingual) neurosurgical patients have been investigated mostly with DCS and fMRI, as highlighted in a very recent review by Polczynska and Bookheimer [ 16 ]. This review suggests several principles concerning languages organization in bilingual patients, which may be useful in predicting the likelihood of separate versus converging representation of languages (i.e., age of L2 acquisition, proficiency level of L2 and linguistic distance between L1 and L2).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed preoperative mapping of the language pathway is mandatory, especially in case of bilingual patients, a peculiar subgroup that can present different patterns of cortical representation of the languages. In fact, the first language (L1) and the second language (L2) are processed both by shared brain areas as well as language-specific areas [ 16 ]. Moreover, even in L1 and L2 shared areas distinct language-specific neural population for the different languages have been identified by rnTMS [ 17 ].…”
Section: Introductionmentioning
confidence: 99%